Implementation of streamlining measures in selecting and prioritising complex cases for the cancer multidisciplinary team meeting: a mini review of the recent developments - Al-Hammouri, Tarek; Almeida-Magana, Ricardo; Soukup, Tayana; Lamb, Benjamin (Frontiers in Health Services, 2024)
In January 2020, NHS England and NHS Improvement, in the United Kingdom, issued a permissive framework for streamlining cancer multidisciplinary (MDT) meetings. Streamlining is defined as a process whereby complex cases are prioritized for full discussion by an MDT in an MDT meeting (MDM), while the management of straightforward cases is expedited using Standards of Care (SoC). SoC are points in the pathway of patient management where there are recognized guidelines and clear clinical consensus on the options for management and should be regionally agreed and uniformly applied by regional Cancer Alliances. While this report marks the first major change in cancer MDT management since the Calman-Hine report in 1995, its implementation, nationally, has been slow. It is argued however that streamlining is a necessary step in ensuring the viability of MDT processes. In this mini review, we offer a succinct summary of the recent developments around the implementation of the 2020 streamlining framework, including challenges and barriers to its implementation, and the potential future directions in this field. We conclude that ensuring successful implementation of the framework and the SOC requires securing a buy-in from key stakeholders, including MDTs and hospital management teams, with clearly defined management approaches that include triage (e.g. through a mini MDT meeting), assessment of case complexity, and roles of the MDT lead and the members, acknowledging that the SOC cannot be universally applied without the consideration of individual variations across teams and hospital Trusts.